Traffic Congestion Articulation Control Using Mobile Cloud Computing: Advancements in Traffic Management using VANET and Mobile Cloud Computing (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Traffic congestion is the biggest problem in both the traffic tools whether adhoc mobile networking or general road traffic system. The continuous advancement in the automotive industry changes the definition of the vehicles. Now vehicles are now coming with equipped sensors and other processing as well communication capabilities. VANET considered as a distinct type of Mobile Ad Hoc Networks, which avoid the jam and articulation situation and moreover save the time by getting guidance from the GPS system about the shortest path from the various algorithm. Even it guide about the road safety issue and destination. It reset the shortest path through various algorithm again and again so that user will not get stuck in the traffic jam. This paper outlines the VANET definition, its architecture and protocols from a research point of view. Although, VANET are a subset of MANET but they are also the future of Intelligent Transport Systems.